2012
DOI: 10.1002/aoc.2908
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative catalysis with binary Lewis acid–Lewis base system for the coupling of carbon disulfide and epoxides

Abstract: The cycloaddition of epoxides with carbon disulfide proceeds effectively by using a binary catalyst system of tetradentate Schiff‐base aluminum complexes (designated as salenAlX) as Lewis acid in connection with a nucleophilic co‐catalyst, such as quaternary ammonium salt. The steric factor of the substituent groups on the aromatic rings of salenAlX and the anion of quaternary ammonium salt all have significant effects on the activity of the binary catalyst system, as well as the selectivities of the resultant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…These results showed that the Co­(III)-based catalyst is unsuitable for the COS/PO copolymerization. Prior to the present study, we utilized a binary system composed of salen-type cobaltate complex and a ionic ammonium salt for mediating the coupling reaction of carbon disulfide and epoxides, but unfortunately, no product was found …”
Section: Resultsmentioning
confidence: 99%
“…These results showed that the Co­(III)-based catalyst is unsuitable for the COS/PO copolymerization. Prior to the present study, we utilized a binary system composed of salen-type cobaltate complex and a ionic ammonium salt for mediating the coupling reaction of carbon disulfide and epoxides, but unfortunately, no product was found …”
Section: Resultsmentioning
confidence: 99%
“…1 The procedures described previously for such a transformation used carbon disulfide in presence of a base and/or catalyst, and included an in situ formation of a xanthogenate or a similar intermediate, and then its reaction with an epoxide 2,[5][6][7][8][10][11][12][13][14] (for a detailed critical consideration of the literature data see ref.…”
Section: Synthesis Of Trithiocarbonatesmentioning
confidence: 99%
“…We did not isolate these compounds, but the formation of some 1,3-oxathiolane-2-thiones in certain conditions was observed previously. 2,5,6,14 It is also known that these compounds react with excess carbon disulfide to give trithiocarbonates. 2,6 Apparently, in our case the subsequent addition of a nucleophile (Nuc = EtOCS 2 -, EtO -, or MeO -from the solvent) to probable intermediates 7 occurred quickly and caused cleavage of the heterocycle.…”
Section: Mechanism and Stereochemistry Of The Reactionmentioning
confidence: 99%
See 2 more Smart Citations